A Heuristic Scheduling Policy for Multi-Item, Multi-Machine Production Systems with Time-Varying, Stochastic Demands - Gonçalves, José F.; Leachman, Robert C.; Gascon, André; Xiong, Zhong K. (Management Science, 1994)
An effective scheduling policy known as the Dynamic Cycle Lengths Heuristic was introduced by Leachman and Gascon in 1988 for the multi-item, single-machine production system facing stochastic, time-varying demands. In this article we develop a heuristic scheduling policy for the multi-machine extension of the same problem. We integrate the concepts of the Dynamic Cycle Lengths Heuristic with a nonlinear integer optimization model to obtain an overall scheduling policy that allocates items to machines and schedules production quantities during the next time period. We report promising performance in limited simulation tests of the policy.